(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate related features of adjacent lateral incisors in unilateral impacted maxillary canine cases by comparing lateral incisor length between the impacted and non-impacted sides, and by examining the association of overlap severity and canine-lateral incisor distance with lateral incisor root resorption on cone-beam computed tomography. Subjects and methods: A cross-sectional analytical study was conducted on 43 unilateral impacted maxillary canine cases assessed on cone-beam computed tomography images. Lateral incisor length was compared between the impacted side and the contralateral side in the same patient. The relationships of overlap severity and canine-lateral incisor distance with the severity of lateral incisor root resorption were analyzed using Spearman correlation. Results: The lateral incisor on the impacted side was significantly shorter than that on the non-impacted side (21.6 ± 3.2 mm vs 22.2 ± 2.4 mm; p = 0.013). Overlap severity showed a positive correlation with root resorption severity (rho = 0.389; p = 0.010), whereas canine-lateral incisor distance showed a negative correlation with root resorption severity (rho = -0.323; p = 0.035). The canine-lateral incisor distance was significantly smaller in the resorption group than in the non-resorption group (p = 0.047). Conclusions: In unilateral impacted maxillary canine cases, the adjacent lateral incisor may demonstrate related morphologic features, and its spatial relationship with the impacted canine is associated with root resorption. Cone-beam computed tomography may be useful for early identification of root resorption risk in adjacent teeth and for pretreatment assessment.